POLA KEMITRAAN STAKEHOLDERS DALAM PROGRAM PENGELOLAAN SAMPAH DI KABUPATEN SEMARANG 2017-2018 (Pengelolaan Sampah Berbasis TPS 3R Di Desa Bergas Kidul) - Wardhani, Putri Puspa; ., Kushandajani (Journal of Politic and Government Studies, 2020)
The 3R TPS-based waste management Program held in Bergas Kidul is anactivity that was first performed in Semarang district so that the government ofSemarang District established TPS 3R in Bergas Kidul village As the TPS 3Rpilot into the background of this research. The problem is: how does therealization of stakeholders mapping in the waste Management program in BergasKidul village in 2017-2018? How is the implementation of partnership amongthe stakeholders in the dumpster 3R-based waste management program in DesaBergas Kidul district of Semarang?The purpose of this research is to know the stakeholders mapping andexplain the stakeholders partnership pattern in the Waste management programin Semarang District in 2017-2018 by taking a case study of the 3R TPS-basedwaste management in the village Bergas Kidul. The research methods used arequalitative research methods with descriptive research type.The results of the study showed the cooperation between the partnershipbetween Semarang District Environmental office and the local communityBergas Sehat Group as the subject of the management of TPS 3R is a productivecooperation. Partnership in the Program TPS 3R Bergas Kidul Run on theprinciple of equality, the existence of the objective and mission in addressing thegarbage problem in Bergas Kidul. Each of the parties involved has also beencarrying out their duties and authorities. Each of the parties involved also benefitfrom the government of Semarang Regency itself has benefited the cost oftransportation costs for the transportation of waste to landfill as well as minimizethe use of landfill Blondo in Bawen, because of garbage can be processed in TPS3R. While the benefits for the community itself, the garbage managed with the3R is able to produce economic value, job creation.Keywords: partnership, waste Management, TPS 3R